Dependence of objectivity in basketball game officiating on the number of referees - Hrusa, P.; Hrusova, D. (Journal of Human Sport & Exercise, 2021)
The aim was to evaluate the level of objectivity of basketball game officiating and find out, if there is a significant difference in dependence on the number of referees. The core of the study was to verify the assumption that three-person officiating (3PO) brings higher objectivity in basketball game officiating, compared to two-person officiating (2PO). The problem was solved by empirical, descriptive and causal research with quantitative and qualitative analysis. 60 selected games (30 2PO and 30 3PO) of the top Czech Basketball Federation (CBF) competition were evaluated. The level of objectivity was evaluated by means of these indicators: number of foul calls, number of referees` mistakes, index of mistakes, and number of off-ball fouls. The statistical significance of the difference was evaluated in Chi-square test (Chi-Quadrat, a .05). Qualitative analysis was based on the minimum required criteria according to expert opinions of top league CBF referees (n = 26). The significant difference in the number of foul calls was not confirmed. The results showed significant difference in decrease of number of referees` mistakes and index of mistakes and in increase of number of off-ball fouls. The findings support the idea of 3PO system to be efficient.